To Identify the Importance of a Mobile Application for Indonesia’s Hidden Beauty - MARTINEZ, Jude Joseph Lamung; HENDIJANI, Roozbeh Babolian (Journal of Environmental Management and Tourism, 2018)
With recent advances in Internet and mobile technologies, there are increasing demands for electronic access to tourist information systems for service coordination in order to provide better experiences for tourists. One of the popular aspects of tourism for tourists is eco-tourism. Unfortunately, most eco-tourism destinations in Indonesia are in obscure or rural areas that are lacking in telecommunication signals as the area. Given the rapid uptake of smartphone technology and associated applications there is a need to evaluate the current and emerging state of the art and what this means for the tourism domain. Therefore, the nature of this study is to know what eco-tourists in Indonesia need from an offline application in the rural areas due to the lack of web access. This study uses quantitative and qualitative research methods. A questionnaire comprising 150 questions was distributed among eco-tourists in Jakarta. Content analysis was conducted among different websites and applications related to tourism in Indonesia. Providing a good experience with useful apps is helpful to motivate tourists to revisit the destination. This platform can be used by practitioners and researchers as a guideline to design usable mobile applications for eco-tourists and other niche segments of tourism.